Legal Critique of the Paradox of Notarial Deed Strength as Authentic Evidence in Civil Disputes Based on Legal Literacy - Nindy Nurfaridah Salsabil; Yanuar Trah Maharani; Juliana Ndruru (Global Action and Education for Society, 2026)
In the context of modern civil legal relations, the demand for written evidence continues to increase alongside the need for legal certainty in socio-economic transactions. A notarial deed, as an authentic instrument, is regarded as having “perfect and binding” evidentiary force because, doctrinally, it rests on three layers of evidentiary strength: outward (external), formal, and material. However, in disputed civil cases, a paradox emerges: a deed designed as perfect evidence may still be rebutted through tegenbewijs, re-evaluated by the judge, and may even be subject to degradation or annulment. This study aims to analyze the meaning of “perfect evidence” and to explain the factors that make the evidentiary force of notarial deeds non-absolute in judicial practice. The method employed is normative legal research using a statutory, conceptual, and descriptive-analytical approach based on library research on the Indonesian Civil Code, the Notary Position Act, legal doctrines, and relevant literature and court decisions concerning deed disputes. The findings show that the “perfection” of a deed is prima facie in nature: it is binding as long as formal requirements are satisfied and not proven otherwise. Procedural defects (reading of the deed, presence of witnesses, and signing) may reduce the deed’s status to a private deed, while material defects such as defects of consent and abuse of circumstances may lead to annulment. Ultimately, the court becomes the final arena for determining the evidentiary force of a deed, while also exposing notaries to potential liability when the procedure and quality of the deed are challenged. This study underscores the need for a systematic interpretation of Article 1870 of the Indonesian Civil Code so that “perfect evidence” is not understood as an absolute force, but as an instrument of legal certainty that still allows corrective mechanisms in the interest of justice.